2017
DOI: 10.1002/sdtp.12048
|View full text |Cite
|
Sign up to set email alerts
|

P‐149: Maximization of Transmittance and Minimization of Image‐Flickering due to Flexoelectric Effect in Low‐Frequency Driving Fringe‐Field Switching (FFS) Mode Using LCs with Negative Dielectric Anisotropy

Abstract: Image-flickering due to flexoelectric effect in a low frequency driven fringe-field switching (FFS) LCD is troublesome. Maximization of transmittance in the FFS mode is achieved using LCs with negative dielectric anisotropy but still the flickering exists. The paper describes in detail on optimal solutions how it can be solved by controlling the ratio of electrode width to distance and thickness of passivation layer. The results greatly contribute to achieve high transmittance and image-flickering free FFS LCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In order to use a low driving frequency to save energy, the image flickering problem must be solved. [9][10][11][12][13][14] In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD. 15 Ions may cause 2 problems.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to use a low driving frequency to save energy, the image flickering problem must be solved. [9][10][11][12][13][14] In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD. 15 Ions may cause 2 problems.…”
Section: Introductionmentioning
confidence: 95%
“…However, if the driving frequency is reduced, there is a problem that the brightness of the display may change with time, a phenomenon known as image flickering. In order to use a low driving frequency to save energy, the image flickering problem must be solved . In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD .…”
Section: Introductionmentioning
confidence: 99%